Efeito da spirulina platensis e do exercício aeróbico no processo de envelhecimento em ratos - Mazzola, Daiane (2011)
The moderate exercise and antioxidants molecules have been reported to prevent ageing associated-chronic disease and also to prolong life in experimental models. However, are still under investigation the biological mechanisms involved and the appropriate conduct for the use of these therapies. In this context, the aim of the present study was to verify the effect of the moderate exercise and the use of the Spirulina platensis in aging in rats. For this, 80 male rats Wistar were divided in adult group (n = 40; 9 month) and young group (n = 40; 5 month), who underwent to treatments: Exercise (E) by swimming during 30 minutes; Spirulina platensis (S) offered by gavage at a dose of 2.6 mg/Kg bw; Exercise plus Spirulina platensis (ES) and Control. All animals received standard chow and water to ad libitum and the treatments occurred during ten weeks, three time a week and once a day. For analysis of lipid peroxidation was analyzed TBARS in brain and serum, and to lipid profile was analyzes total cholesterol (TC) and triglyceride (TG) in serum. The results indicate brain TBARS in young was less in ES than control or S (both, P < 0.0001) and E than control (P = 0.0014) or S (P < 0.0001). In adults, E was higher than control (P = 0.0064). Young treated with ES decreased serum TBARS (P = 0.008) and adults increased in control (P = 0.0003), E, S (P < 0.0001) and ES (P = 0.0012). In young, the cholesterol increased in control (P < 0.0001), E (P = 0.0156) and S (P = 0.0026). TG decreased in control (P = 0.0003), E, S (P < 0.0001) and ES (P = 0.0012). These findings support the conclusion that adult animals have different lipid and biochemical responses of young. From this, becomes necessary the appropriateness of physical exercise protocols and different dosages of Spirulina platensis for different age groups to promote health throughout the aging process